PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBENTUK PERMAINAN CARD SORT TERHADAP HASIL BELAJAR SEJARAH SISWA KELAS XI IPS SMA NEGERI 6 MUARO JAMBI - David Umar, Satrio Pamungkas (Universitas Batanghari Jambi, 2018)
Abstract Students can achieve maximum learning outcomes when a teacher appropriately implements teaching media. For that we need an innovative learning media and able to increase the activity and student learning outcomes. Learning media that meet these criteria one of them is the learning media in the card sort game. This research uses quasi-experimental method with pretest-postest design. The subjects of this study were class XI IPS which was divided into two groups namely experimental group (XI IPS 4) and control group (XI IPS 3), with data processing technique using t-test on average of student learning result of history subjects.The result of t-test is thitung = 2.517 and ttable = 1.666 it states that H0 is rejected and Ha is accepted, because the experimental group learning result is 73,92> 68,91 control group. So it can be concluded that there is influence of learning media in the form of card sort game on student learning result of history subject. Keywords: Media, Card Sort, Learning outcomes